Marking to market and inefficient investment decisions - OTTO, Clemens A. (Institutional Knowledge at Singapore Management University, 2018)
We examine how mark-to-market accounting affects the investment decisions of managers with reputation concerns. Reporting the current market value of a firm’s assets can help mitigate agency problems because it provides outsiders (e.g., shareholders) with new information against which the management’s decisions can be evaluated. However, the fact that the assets’ market value is informative can also have a negative side effect: managers may shy away from investments that indicate conflicting private information and would damage their reputation. This effect can lead to inefficient investment decisions and make marking to market less desirable when market prices are more informative.